Numerical simulation of coupled liquid water, stress and heat for frozen soil in the thawing process. Issue 4 (15th November 2021) - Xiao, Wei; Liu, Enlong; Yin, Xiao; Zhang, Guike; Zhang, Chong; Yu, Qihao
Abstract : Purpose: The purpose of this paper is to perform the thermo-hydro-mechanical (THM) numerical analysis in order to study the thawing process for frozen soil and to predict the thawing settlement. Design/methodology/approach: A new one-dimensional multi-field physical coupled model was proposed here to describe the thawing process of saturated frozen soil, whereby the void ratio varied linearly with effective stress (Eq. 10) and hydraulic conductivity (Eq. 27b). The thawing process was simulated with different initial and boundary conditions in an open system with temperature variations. The mechanical behavior and water migration of the representative cases were also investigated. Findings: The comparisons of representative cases with experimental data demonstrated that the model predicts thawing settlement well. It was found that the larger temperature gradient, higher overburden pressure and higher water content could lead to larger thawing settlement. The temperature was observed that to distribute height linearly in both frozen zone and unfrozen zone of the sample. Water migration forced to a decrease in the water content of the unfrozen zone and an increase in water content at the thawing front. Research limitations/implications: In this study, only the one-directional thawing processes along the frozen soil samples were investigated numerically and compared with test results, which can be extended to two-dimensional analysis of thawing process in frozen soil. Originality/value: This study helps to understand the thawing process of frozen soil by coupled thermo-hydro-mechanical numerical simulation.